Analysis of high temperature steam oxidation of superheater steels used in coal fired boilers - Dudziak, T.; Lukaszewicz, Mikolaj; Simms, Nigel J.; Nicholls, John R. (Springer, 2015)
The present work compares the behaviour of four steels: (T23, T92, T347HFG, Super304H) in the temperature range 600–750 °C. This study focuses on the analysis of the oxidation kinetics in terms of mass change, metal loss and thickness change of the selected materials. In order to understand the differences in oxidation rates between the selected steels, the impact of chromium and the alloying elements were considered in this work. The obtained results show that the impact of alloying elements differs with exposure conditions and importance of the synergy effect.
Keywords: Steam oxidation; Ferritic steels; Austenitic steels; High temperature; EDX; SEM; Coal power plant